Mapping and Capturing the Soundscape, and Biodiversity for Special Environmental Education. Case Study for Zakynthos Sea Park - Μινώτου Χαρίκλεια; Παρασκευόπουλος Στέφανος (Education Sciences, 2020)
Environmental education for people with disabilities is the subject of this study. The issues of protected areas, threatened species and the management and conservation of environmentally important habitats are priorities for the creation of environmental educational material adapted for visually impaired people, hearing problems and moving difficulties and disabilities problems. The scientific fields of acoustic ecology and conservation education have been used to achieve the virtual transfer of the participants to the selected ecosystem, namely the Carettacaretta reproduction area in the Zakynthos Sea Park and the understanding of the identity and environmental value of the protected area. The evaluation of the environmental educational material was based on data from two questionnaires from 46 participants and their 11 teachers and the notes from two observers.